First data about finds of a rare fungus Battarrea phalloides (Dicks.) Pers. from the Kharkiv Forest-steppe - Akulov, O.; Gromakova, A.; Zhezhera, M.; Tupikov, A. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
During 2016 a rare gasteroid fungus Battarrea phalloides (Dicks.) Pers. was found twice in the Kharkiv Forest-steppe. The first finding was registered in the National Nature Park «Homilsha Forests» (Zmiiv district), the second – from upland areas of ravine forest near Dvorichna town, on lands projected for inclusion to the National Nature Park «Dvorichansky» (Dvorichna district). These are the first finds of the fungus in the Kharkiv Forest-steppe. A detailed description of species, as well as its ecological and sozological properties are given. Summarized data about the distribution of B. phalloides in Ukraine are presented basing on the analysis of published data, as well as on revision of materials from the Mycological Herbaria CWU (V.N.Karazin Kharkiv National University), KW (M.G.Kholodny Institute of Botany, NAS of Ukraine) and LE (V.L.Komarov Botanical Institute, Russian Academy of Sciences). The collected samples were included in scientific mycological herbarium of V.N.Karazin Kharkiv National University CWU (Myc). As a result of the analysis of the Ukrainian finds it was confirmed that studied species can be used as an indicator of arid and semiarid biotopes. However, since it often develops in anthropogenically transformed landscapes, the question of whether it should be included in the Red Lists remains controversial.